Taxonomic and ecological analysis of vascular plants of the pine forest of the Irtysh Region - Yelkenova, B.Z.; Beisenova, R.R. Beisenova; Karipbayeva, N.V.; Polevik, V.V. (Fundamental and Experimental Biology, 2022)
The article presents a taxonomic, biomorphological, geographical analysis of the biodiversity of the flora of herbaceous species of pine forests of the Irtysh region, which is represented by 168 plant species belonging to 116 genera and 42 families. Analysis of the largest flora families of herbaceous species shows that the dominant communities are Artemisia L. — Festucaria Heist. ex Fabr. and Artemisia L. — Poaceae Barnhart (Artemisia L., Festuca Heist. ex Fabr., Stipa capillata L.) phytocenoses. In all the studied sites, the following plant species are dominates or codominants of Festuca rupicola Heuff., Agropyron cristatum (L.) Gaertn., Stipa capillata L., Artemisia vulgaris L., Carex supina Willd. ex Wahlenb., Spiraea hypericifolia L. The flora is based on angiosperms, including dicotyledons — 137 species (81 %); monocotyledons — 28 species (16.6 %). Gymnosperms are represented by two species of Pinus sylvestris L., Juniperus sabina L., and there is also one species of Eguisetum arvense L. horsetail. The richness of the flora is also emphasized by some quantitative indicators of its taxonomic composition: the average species saturation of one family is 4, the maximum is 36. There are 9 rich families with the number of species above the average (21.4 % of the total number of families), and 22 the poorest, single — species families (52.3 %). The top ten leading families contain 71 % of the total floral diversity. The high level of floristic diversity of the studied territory is due to the variety of ecological conditions of plant habitats (the valley of the Irtysh River with a high variation in moisture and salinity, a variety of rocks of the adjacent riverside uplands) and anthropogenic activities leading to an increase in weed and adventitious plant species.